Nematode functional traits and community structure change from river to the terrestrial border in Segara Anakan Mangrove, Indonesia - ARDHINI RIN MAHARNING; ERWIN RIYANTO ARDLI; ROMANUS EDY PRABOWO (Society for Indonesian Biodiversity, 2023)
Abstract. Maharning AR, Ardli ER, Prabowo RE. 2023. Nematode functional traits and community structure change from river to the terrestrial border in Segara Anakan Mangrove, Indonesia. Biodiversitas 24: 2434-2446. We intended to explore the spatial distribution of nematode functional traits and community structure in Segara Anakan Mangrove, Indonesia. Samples were retrieved from 14 stations, extending from the river to the area adjacent to terrestrial forest. We used taxonomic and functional trait identification, covering body shape, length, tail shape, feeding type, and life history as independent traits, and combined traits by collecting traits describing individual nematodes. The principal component analysis suggested that predatory or omnivorous or long-size nematodes mainly inhabited stations adjacent to the terrestrial forest but were unclear for the mid-stations. There were 29 combined traits and 38 genera of nematodes observed. The detrended correspondence analysis revealed that nematode compositional changes from the river to the terrestrial adjacent area were clearer for the combined traits and nematode genera. Seven combined traits and 12 genera inhabited only the particular stations of the study site. The common nematodes were slender, 1-2 mm long, elongated filiform tails, non-selective deposit feeders, and very tolerant to pollutants, which lived in almost all stations (92.86%). The genus relative abundance (>10%) included Anoplostoma, Eubostrichus, and Chromadorina. The results suggest that distance from the river might regulate the habitability of nematodes, in which nematode functional traits play roles.